TECHNIQUE OF TRANSLATION IN “SHANG-CHI AND THE LEGEND OF THE TEN RINGS” FILM - Bambang Eko Siagiyanto; Fitri Palupi Kusumawati; Refa'i M.Pd.; Adjeng Sagieta Aultya (Journal of English Education and Entrepreneurship (JEEP), 2023)
Translation is the communication of meaning from one language (source language) to other language (target language). It is a process of transferring the ideas, meaning or message obtained from source language into target language. This research was aimed to find out the translation techniques used by the translator in translating subtitle of Shang-Chi and the Legend of the Ten Rings movie. It was aimed to find out the most dominant type of translation technique used in the subtitle. This research method is qualitative research. The theory used to analyze the translation technique is Molina and Albir (2002). The results of this study the total of all translation techniques is 288 consisted of Borrowing 0.34%, Calque 2.43%, Discursive creation 3.81%, Established equivalent 5.20%, Linguistic amplification 6.59%, Linguistic compression 14.23%, Literal translation 49.30%, Modulation 5.90%, Reduction 6.94%, and Transposition 5.20%. From these results, it can be concluded that the most dominant translation technique used by the translator was a literal translation.